Sleep in Autism - Maxwell-Horn, Angela; Malow, Beth A. (Seminars in Neurology, 2017)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that has increased in prevalence over the last several decades. A significant proportion of children with ASD have comorbid sleep disorders. The interplay between ASD and sleep is multifactorial and bidirectional. There is evidence for physiological differences in ASD that contribute to sleep problems, including sensory overresponsiveness (SOR) and abnormal melatonin production. Comorbidities associated with ASD (attention deficit hyperactivity disorder [ADHD], mood disorders) as well as medications used to treat these comorbidities often have effects on sleep architecture. In this article the authors discuss the etiology and manifestations of sleep disorders in children with ASD, as well as their clinical evaluation and treatment options.
Keywords: autism; sleep; neurodevelopmental disorders